Maxillary osteomyelitis induced by rhinosinusal mucormycosis in a tropical country - Pulino, Bianca de F. B. [UNESP]; Guerra, Raphael C. [UNESP]; dos Santos, Déborah L. [UNESP]; Faverani, Leonardo P. [UNESP]; Hochul-Vieira, Eduardo [UNESP] (Wiley, 2021)
Mucormycosis is an opportunistic, and frequently lethal, fungal infection that occurs in patients with immunocompromised states, such as diabetes mellitus. This infection invades not only the paranasal sinuses, but also the maxillae, zygoma, and rhinocerebral structures, which results in massive destruction of the facial skeleton and soft tissue. It progresses in patients with underlying comorbidities, such as diabetes mellitus, haematologic malignancy, cerebral malignancy, renal failure, and systemic immunosuppression. Most cases occur in tropical countries. The relationship between mucormycosis and these underlying conditions has been widely discussed in the literature. This study sought to report the case of a patient diagnosed with glioblastoma and mucormycosis in the maxilla, who was successfully treated with surgery and isavuconazonium sulfate (Cresemba).
Keywords: glioblastoma; infections; maxilla; mucormycosis